Egypt, Arab Republic : Accounting and Auditing - World Bank (Washington, DC, 2013)
During the past decade, Egypt made significant efforts to align corporate financial reporting requirements with the International Accounting Standards (IAS) and to close the compliance gap in both accounting and auditing practices. Consequently, important improvements have been achieved in accounting and disclosure requirements for the publicly traded companies and financial institutions and in Egyptian Accounting Standards as benchmarked against IAS. Moreover, a new Accounting Practice Law has been drafted and agreed upon by all stakeholders, though not yet been ratified. Further improvements could be achieved by issuing a modern legislative framework that includes an appropriate regulatory framework for practicing auditors, addressing weaknesses in professional education and training arrangements, introducing qualification examinations for auditor licensing, and developing an enforcement mechanism to ensure compliance with applicable accounting and auditing standards.